ANALISIS KECUKUPAN MODAL PADA BANK KONVENSIONAL DI INDONESIA - Fitri Abriani Jinggili; Mardi Mardi; Santi Susanti; Dwi Kismayanti Respati (Jurnal Akuntansi dan Pajak, 2022)
The problem is still found disparity in the results of research on capital adequacy in conventional banks in Indonesia, therefore conducted testing the influence of rentability, liquidity, and business efficiency on capital adequacy in conventional banks in Indonesia. The research using quantitative methods on 87 Conventional Banks with purposive sampling techniques 4 criteria, so that obtained 71 samples of conventional banks. The data in this research is secondary data from the annual reports of conventional banks in the 2019 period. The research method used is multiple linear regression analysis. This research concluded that rentability, liquidity, and business efficiency are considered to be the dominant and significant factors influencing and improving capital adequacy in Conventional Banks. Therefore, this research focuses any factors to know influence on capital adequacy. This is because capital adequacy has a very important function in carrying out operational activities Keywords: Conventional Banks, Rentability, Liquidity, Business Efficiency, Capital Adequacy